Ulnar Head Replacement and Related Biomechanics - Sauerbier, Michael; Arsalan-Werner, Annika; Enderle, Elena; Vetter, Miriam; Vonier, Daniel (Journal of Wrist Surgery, 2013)
A stable distal radioulnar joint (DRUJ) is mandatory for the function and load transmission in the wrist and forearm. Resectional salvage procedures such as the Darrach procedure, Bowers arthroplasty, and Sauvé-Kapandji procedure include the potential risk of radioulnar instability and impingement, which can lead to pain and weakness. Soft tissue stabilizing techniques have only limited success rates in solving these problems. In an attempt to stabilize the distal forearm mechanically following ulnar head resection, various endoprostheses have been developed to replace the ulnar head. The prostheses can be used for secondary treatment of failed ulnar head resection, but they can also achieve good results in the primary treatment of osteoarthritis of the DRUJ. Our experience consists of twenty-five patients (follow-up 30 months) with DRUJ osteoarthritis who were treated with an ulnar head prosthesis, with improvement in pain, range of motion, and grip strength. An ulnar head prosthesis should be considered as a treatment option for a painful DRUJ.
Keywords: distal radioulnar joint (DRUJ); osteoarthritis; arthroplasty; ulnar head resection; ulnar head prosthesis